Exploring the role of glutathione therapy in schizophrenia: a case report - Pehlivan, Rana; Pasquali, Marco Antonio Batisti; Parikh, Parinda (International Journal Of Community Medicine And Public Health, 2025)
Schizophrenia is a psychiatric disorder consisting of debilitating symptoms. Accumulating evidence suggests that oxidative stress is one of the main mechanisms of pathogenesis, and patients with schizophrenia have lower levels of glutathione, a crucial antioxidant. In this case, we present a 23-year-old male with severe schizophrenia who was undergoing treatment with multiple antipsychotics but showed minimal improvement in general psychopathology on the Positive and Negative Syndrome Scale (PANSS). Given that the patient was on numerous medications, we introduced glutathione as a novel approach. We hypothesize that glutathione is an antioxidant that reduces oxidative stress and enhances the overall functioning of schizophrenia patients. We administered weekly glutathione treatment for 10 weeks. Our findings suggest that glutathione as an adjunct therapy significantly improves symptoms in patients with schizophrenia. No important adverse effects occurred during follow-up.